Provably-Secure LED Block Cipher Diffusion and Confusion based on Chaotic Maps - Al-Saadi, Hussain M.; Alshawi, Imad (Informatica, 2023)
Lightweight cryptography algorithms have concentrated on key generation's randomness, unpredictable nature, and complexity to improve the resistance of ciphers. Therefore, the key is an essential component of every cryptography algorithm since it affects the algorithm's level of security. Light Encryption Device (LED) is a high-performance, lightweight block encryption solution that works on resource-constrained devices and considers a lighter version of AES. It employs a 64-bit block cipher with two significant instances using 64-bit and 128-bit keys, respectively. A lack of key scheduling in LED heightens security risks, such as key-related attacks. Specifically, now that LED has been hacked and is no longer secure. Therefore, LED must achieve a high diffusion and confusion level to withstand known attacks. Chaos-based encryption provides an exceptionally high level of security because of the unique characteristics of chaotic systems, which are defined by various nonlinear deterministic dynamic equations. Merge LED algorithm and the advantages of chaotic maps randomness provide successful confusion and diffusion property to improve the LED algorithm's shortcomings by increasing its security. This paper presents a lightweight approach to construct a robust, sufficiently using 3-D Lorenz system chaotic map to generate a one-time pseudo-random bit key to avoid being predicted by adversaries, resulting in achieving sound confusion and diffusion and withstand known assaults. A NIST test suite found that the performance of the LED based on the 3-D Lorenz chaotic map approach in terms of data secrecy is nearly 0.3003 higher than that of the LED and keeps the trade-off between computation cost and security.